Impact of Salinity Stress on Germination and Growth of Pea (Pisum sativum L) Plants - Ehtaiwwesh , Amal F; Emsahel, Munira J (Al-Mukhtar Journal of Sciences, 2020)
The aim of the present study was to evaluate the effects of salinity stress on germination and growth of pea (Pisum sativum L) plants. A laboratory experiment was conducted to evaluate the effect of salinity stress on germination and growth of pea Pisum sativum L plant. Seeds of pea were sown in Petri dishes and pots and treated with four different levels of salinity (0, 50, 100, and 150mM NaCl) with completely randomized designs in four replications. Results revealed that seeds of pea were able to germinate at low salinity levels (NaCl 50mM NaCl) without a significant decrease in germination and growth traits, at the same time as a severe decrease in those traits were recorded at higher levels of salinity (100 and 150mM NaCl). The results indicated that seed germination and seedling establishment were inhibited due to the decrease of water potential, which results in the decline in water uptake by seeds, and seed germination was prevented by a high level of salinity stress (150mM NaCl). The results pointed out that germination percentage (GP), mean daily germination (MDG), germination speed (GS), and vigor index (SVI) varied under moderate and high salinity levels. All the studied parameters were reduced with increasing the NaCl level. The max and min GP, MDG, GS, and SVI were observed under control conditions (0mM NaCl) and highest salinity level (150mM NaCl) respectively. The same trend was seen in plant growth traits including: plant height, branch number, leaf number, leaf area, and shoot fresh and dry weight. The results provided important reference information for research on the impact of salinity on germination and growth of pea.